REDESAIN TANDU UNTUK MENDUKUNG MOBILITAS DAN PENYIMPANAN MENGGUNAKAN TRIZ - Susatyo Nugroho W.P; Denny Nurkertamanda; Dhani Mahendra (TEKNIK, 2011)
Most Victims Of Accidents That Occur In Mountainous areas is injured in fractures and spinal injuries. Spinalinjury itself should be evacuated using a spinal stretcher, but because of its shape, difficult spinal stretcher wasbrought to the location of the disaster. While the standard stretcher has the ease of mobilization but it cannotaccommodate victims with spinal injuries. On the other hand, power and heavy litter becomes a veryimportant factor in the development of this litter product.The purpose of this study was to develop a standard stretcher that can be used to accommodate all types ofinjuries and a strong stretcher and rigan. TRIZ is used to resolve the contradictions that occurred. After a seriesof studies produced improvements in the standard litter that can accommodate victims of spinal injury whileprovding ease of mobilization for evacuation and storage process. And produced tools to maximize the use ofstretchers.